2016
DOI: 10.1093/forestry/cpw049
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in the flora of oak forests and of oak:spruce mixtures following removal of conifers

Abstract: Ground vegetation changes under coppice regimes have been well described but less work has been done in Britain on the changes that take place under managed high-forest. In 1982/3 15 sixty 14.1 x 14.1 m quadrats were recorded across stands of oak (Quercus robur L.) and spruce (Picea abies (L.) H.Karst.)/oak mixtures, of various ages in Salcey Forest, southern England. In 2014 the survey was repeated and changes in the ground flora over this 31year period in the different crop types were compared. There was a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Kirby and May (1989) found increases in species richness and ground cover in the first few years in restored stands at Dalavich Wood in Argyll, suggesting that restoration could be successful. Similarities between restored and remnant oak stands in terms of species richness and the type of species present have since been found at Salcey Forest, Northamptonshire, in a parallel study to this one (Kirby et al, 2017). There was little indication at Salcey that woodland specialists had changed in abundance differently to other species and at Shabbington Woods the specialists were the most likely group to be found in both surveys.…”
Section: Has Broadleaved Woodland Restoration Benefitted the Ground Fsupporting
confidence: 58%
See 1 more Smart Citation
“…Kirby and May (1989) found increases in species richness and ground cover in the first few years in restored stands at Dalavich Wood in Argyll, suggesting that restoration could be successful. Similarities between restored and remnant oak stands in terms of species richness and the type of species present have since been found at Salcey Forest, Northamptonshire, in a parallel study to this one (Kirby et al, 2017). There was little indication at Salcey that woodland specialists had changed in abundance differently to other species and at Shabbington Woods the specialists were the most likely group to be found in both surveys.…”
Section: Has Broadleaved Woodland Restoration Benefitted the Ground Fsupporting
confidence: 58%
“…In the Shabbington Woods and in a parallel study at Salcey Forest (Northamptonshire) (Kirby et al 2017) reductions in species-richness at the quadrat were observed in more stands than showed gains in species. This parallels declines reported for largely-unmanaged broadleaved woods across England based on a comparision of records from 1971 and 2001 (Kirby et al, 2005), and at Sheephouse Wood which was sampled more regularly from 1981 to 2012 (Kirby, 2015).…”
Section: Changes In Species-richness and Disturbance Through The Forementioning
confidence: 88%
“…Despite the short duration of our study relative to the timescales of woodland establishment, vegetation in the former plantation showed development towards a species assemblage characteristic of the remnants. Such an outcome has been shown to take place over periods of a century or more (Kolk and Naaf 2015;Naaf and Kolk 2015) but as Kirby et al (2017) reported, ground flora resembling that of an oak woodland developed over a period of c.30 years close to rows of oaks, following restoration of mixed, Norway spruce (Picea abies)-oak woodland. From this, we conclude the proximity of remnants to former plantation at our study site is enhancing the rate of indicator plant colonization.…”
Section: Restoring the Characteristic Assemblage Of Species Of The Re...mentioning
confidence: 90%
“…Restoration success is frequently assessed using vascular plant species (e.g. woodland canopy species and ground flora) and diversity, and occasionally by use of growth form and growth traits to elucidate succession and community function (Grime 1977;Polley et al 2005;Pfestorf et al 2013;Kirby et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation